Abnormal vocal cord movement treated with botulinum toxin in patients with asthma resistant to optimised management. Issue 4 (23rd March 2014) - Baxter, Malcolm; Uddin, Nizam; Raghav, Sanjay; Leong, Paul; Low, Kathy; Hamza, Kais; Holmes, Peter W.; Hamilton, Garun; Thyagarajan, Dominic; Lau, Ken; Bardin, Philip G.
Abstract Background and Objective Abnormal vocal cord movement may coexist with asthma and cause additional upper/middle airway obstruction. The condition may be a form of muscular dystonia that could contribute to asthma resistant to optimised treatments. Botulinum toxin causes temporary paralysis of muscle and may be an effective local treatment that improves asthma control. Methods In an observational study, we evaluated the benefits of unilateral vocal cord injection with botulinum toxin in 11 patients (total 24 injections). Subjects had asthma resistant to optimised treatment and abnormal vocal cord movement. Responses after botulinum toxin treatment were assessed using asthma control test (ACT) scores, vocal cord narrowing quantified by computerised tomography (CT) of the larynx and spirometry. Side‐effects were recorded. Results ACT scores improved overall (9.1 ± 2.4 before and 13.5 ± 4.5 after treatment; difference 4.4 ± 4.2; P < 0.001). There was also an improvement in airway size on CT larynx (time below lower limit of normal at baseline 39.4 ± 37.63% and improved to 17.6 ± 25.6% after injection; P = 0.032). Spirometry was not altered. One patient experienced an asthma exacerbation but overall side‐effects were moderate, chiefly dysphonia and dysphagia. Conclusions Although a placebo effect cannot be ruled out, local injection of botulinum toxin may be an effective treatment for intractable asthma associated with abnormal vocal cord movement. Further mechanistic studies and a double‐blind randomised controlled trial of botulinum toxin treatment are merited.